Lessons on Peruvian wart or "disease Carrion" - Arce, Julián (1918)
Malignant wart, is, as its name implies, the way hypertoxic, violent and often fatal, Peruvian wart or Carrion's disease. Individualized for the first time in 1870, when fatty epidemically in camps for railroad workers to La Oroya, located in the valleys between chosica and Matucana, was then given the name of Oroya fever to distinguish malaria eruptive wart, typhoid and other diseases, along with her reigned in these regions. Later, in 1885, the unexpected result of the memorable experience of carrion, came to demonstrate the etiological unity of Oroya fever and eruptive wart held hypothesis by Spinal Doctor in 1871.